International Production Networks: The Role of East Asia - Mazitova, Marina; Dyomina, Yana (Prostranstvennaâ ékonomica, 2017)
The authors propose a concept of international production integration which considers international production networks (IPNs) as multi-dimensional structures with relational links and consisting of chains (goods, value creation, etc.), characterized by linear connections. Formation and functioning of IPNs are subject to economies of scale and are well described by the theory of fragmentation. When analyzing the functioning of IPNs considerable attention needs to be devoted to the relative composition of trade flows they generate with respect to inter- and intra-industry trade. The authors classify production networks by their spatial scale into two types: regional and global. Then the researchers verify the hypothesis that the majority of East Asian IPNs are global. This hypothesis is confirmed using the analysis of foreign trade and investment flows. The analysis of foreign trade statistics of individual countries (China, Cambodia and Vietnam) and certain industries (textiles, clothing and leather) using the regional trade intensity index (RTII) shows that the prevailing part of IPNs in mentioned countries as well as in selected sectors are global IPNs, that is, the hypothesis is fully confirmed. At the same time RTII dynamics demonstrates that a growing number of China's IPNs are turning towards the global type; on the contrary, a growing number of Cambodia's IPNs are transforming to the regional type; and there are two opposite trends in Vietnam: a growing number of IPNs in textiles, clothing and leather goods are tend towards the regional type but when considering the industry as a whole a growing number of IPNs are becoming global. The majority of East Asian IPNs in textiles, clothing and leather goods are global due to the fact that these networks are controlled by global brands (mainly of European and American origin)